Manajemen Pendidikan Keagamaan Nonformal bagi Lansia untuk Mewujudkan Resiliensi Sosial dan Active Aging - Lu’luatun Nadiyah; Nailatul Muna (Institut Agama Islam Syubbanul Wathon Magelang, 2026)
This study aims to analyze the implementation of educational management functions (planning, organizing, actuating, and controlling) as well as the supporting and inhibiting factors at the At-Taqwa Quranic Education Center (TPQ) for the elderly in Magelang. A qualitative approach with a descriptive case study method was employed. Data were gathered through semi-structured interviews with four key informants, non-participant observation, and documentation, then analyzed using Miles and Huberman’s interactive model. The findings reveal that educational management at TPQ At-Taqwa undergoes fundamental modifications to align with adult learning principles (andragogy). Planning and organizing functions leverage religious social capital and utilize digital communication platforms. In the actuating phase, a radical curriculum modification is applied by eliminating writing and arithmetic, focusing instead on repetition, listening methods, and psychological motivation to reduce the students' inferiority complex. The controlling function shifts from rigid administrative paperwork to an informal-organic approach aimed at maintaining learning ecology and sustainability. The primary barriers include the biological decline and health vulnerabilities of the elderly, alongside non-formal administrative limitations. In conclusion, the integration of andragogi-based management with structural flexibility and methodological adaptation is the critical success factor in managing religious education for elderly communities.